STATE VS EMPIRE: POWER AND ITS IMPLEMENTATION IN THE FRAMEWORK OF GLOBALIZATION - Запорожченко, Р. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
In the present paper, we analyze theoretical and methodological concepts of state power through the prysm of the category of sovereignty. The main approaches towards defining sovereignty are outlined. The implementation of power is compared in the state and in the empire based on chosen structural and functional parameters. The influence of globalization processes on the transformation of power systems nowadays is studied.